2008
DOI: 10.3892/ijo.32.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Balanitin-6 and -7: Diosgenyl saponins isolated from Balanites aegyptiaca Del. display significant anti-tumor activity in vitro and in vivo

Abstract: Balanites aegyptiaca is a widely distributed African plant of medicinal interest containing a number of cytotoxic and cytostatic compounds. The studies reported here have attempted to further characterize the anti-cancer activity of a mixture of steroidal saponins: balanitin-6 (28%) and balanitin-7 (72%) isolated from Balanites aegyptiaca kernels. The balanitin-6 and-7 mixture (henceforth referred to as bal6/7) has demonstrated appreciable anti-cancer effects in human cancer cell lines in vitro. Bal6/7 display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 38 publications
2
55
0
1
Order By: Relevance
“…Bal6/7 demonstrated IC 50 in vitro growth inhibitory concentrations in U373 GBM and A549 NSCLC cells quite similar for those observed here for ISP, i.e., 0.3 μM (Bal6/7) versus 0.8 μM (ISP) in A549 NSCLC cells and 0.5 μM (Bal6/7) versus 0.8 μM (ISP) in U373 GBM cells (30). Bal6/7 exerts its anti-cancer effects without inducing apoptotic cell death (30), but its in vitro anti-cancer activities result at least partly from depletion of [ATP] i , leading in turn to major disorganization of actin cytoskeleton, ultimately resulting in the impairment of cancer cell proliferation (at the level of cytokinesis) and migration (30). In contrast to a number of natural products acting as anti-cancer agents, bal6/7 does not induce an increase in intra-cellular reactive oxygen species (30).…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Bal6/7 demonstrated IC 50 in vitro growth inhibitory concentrations in U373 GBM and A549 NSCLC cells quite similar for those observed here for ISP, i.e., 0.3 μM (Bal6/7) versus 0.8 μM (ISP) in A549 NSCLC cells and 0.5 μM (Bal6/7) versus 0.8 μM (ISP) in U373 GBM cells (30). Bal6/7 exerts its anti-cancer effects without inducing apoptotic cell death (30), but its in vitro anti-cancer activities result at least partly from depletion of [ATP] i , leading in turn to major disorganization of actin cytoskeleton, ultimately resulting in the impairment of cancer cell proliferation (at the level of cytokinesis) and migration (30). In contrast to a number of natural products acting as anti-cancer agents, bal6/7 does not induce an increase in intra-cellular reactive oxygen species (30).…”
Section: Discussionsupporting
confidence: 63%
“…Bal6/7 exerts its anti-cancer effects without inducing apoptotic cell death (30), but its in vitro anti-cancer activities result at least partly from depletion of [ATP] i , leading in turn to major disorganization of actin cytoskeleton, ultimately resulting in the impairment of cancer cell proliferation (at the level of cytokinesis) and migration (30). In contrast to a number of natural products acting as anti-cancer agents, bal6/7 does not induce an increase in intra-cellular reactive oxygen species (30). In the present study, while we observed transient ISP-induced decreases in [ATP] i in U373 GBM cells, a feature that could explain (at least partly) ISP-induced proapoptotic effects in these U373 cells, we did not observe ISP-induced decrease in [ATP] i nor induction of apoptosis in A549 NSCLC cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23 Suppressed tumor growth was also observed for other saponins like 51,52 and several other saponins. 52,53,[70][71][72][73][74][75][76][77][78][79] A further prominent feature of saponins is their antimicrobial activity. Diosgenyl 2-amino-2-deoxy-beta-D-glucopyranoside was medically active against Staphylococcus aureus and Enterococcus faecalis in a wound model simulating surgical site infections in BALB/c mice.…”
Section: Efficacy Of Saponins and Clinical Potentialmentioning
confidence: 99%